Association between abnormal lipid metabolism and tumor - Li, Chunyu; Wang, Fei; Cui, Lili; Li, Shaoxin; Zhao, Junyu; Liao, Lin (Frontiers in Endocrinology, 2023)
Metabolic Reprogramming is a sign of tumor, and as one of the three major substances metabolism, lipid has an obvious impact. Abnormal lipid metabolism is related to the occurrence of various diseases, and the proportion of people with abnormal lipid metabolism is increasing year by year. Lipid metabolism is involved in the occurrence, development, invasion, and metastasis of tumors by regulating various oncogenic signal pathways. The differences in lipid metabolism among different tumors are related to various factors such as tumor origin, regulation of lipid metabolism pathways, and diet. This article reviews the synthesis and regulatory pathways of lipids, as well as the research progress on cholesterol, triglycerides, sphingolipids, lipid related lipid rafts, adipocytes, lipid droplets, and lipid-lowering drugs in relation to tumors and their drug resistance. It also points out the limitations of current research and potential tumor treatment targets and drugs in the lipid metabolism pathway. Research and intervention on lipid metabolism abnormalities may provide new ideas for the treatment and survival prognosis of tumors.